Sustainable Research of Land Optimization in a Semiarid Sandy Area Based on Soil Moisture Characteristics - Zhang, Hongfei; Cai, Zhaoyang; Chen, Jingyuan; Xu, Yan; Zhang, Fengrong (Frontiers in Environmental Science, 2022)
Land optimization is a necessary means to improve the land use efficiency and promote the sustainable use of land resources. How to fully consider the regional background conditions and scientifically and comprehensively achieve the sustainable and optimal utilization of land resources is a necessary means to promote the sustainable utilization of land resources, especially in semiarid sandy areas with fragile ecological environments. Therefore, based on the characteristics of a semiarid sandy area and by using existing research, with important water resources as the core, this study constructed an optimal land allocation method in a semiarid sandy area based on the soil moisture characteristics. By taking the Horqin Zuoyihou Banner in the semiarid sandy area of China as a typical case, we explored its soil moisture characteristics and influencing factors and put forward the distribution patterns and suggestions for optimal land use. The results show that it is effective to optimize the land space allocation in semiarid sandy areas based on the soil moisture characteristics, and the corresponding land use activities should be arranged according to the moisture conditions of each region, which is beneficial to achieve sustainable semiarid sandy land use. We hope that this study can provide valuable sustainable land optimization solutions for the efficient, sustainable use and protection of land resources in semiarid regions.